Therapeutic challenges in pregnant women with paroxysmal nocturnal hemoglobinuria: A case report. Issue 36 (September 2018) - Bastos, Juliana Marques Coelho; Pinheiro, Patrícia Leal; Rocha, Lissa Canedo; Bicalho, Elisa Cao; Cazeli, Alessandra Barbosa; Marcondes, Síbia Soraya; Pinasco, Gustavo Carreiro
Abstract: Introduction: Paroxysmal nocturnal hemoglobinuria (PNH) is a rare acquired disease, arising from the mutation of clonal hematopoietic stem cells, with an estimated incidence of 1 to 5 cases per million individuals. In pregnant women, adequate information regarding the prevalence of PNH is lacking, and its management has been a challenge because of the significant complications in this group. The condition is diagnosed based on clinical findings and laboratory tests. Eculizumab, the drug of choice for the treatment of PNH, reduces hemolysis and stabilizes hemoglobin levels, thereby decreasing the need for blood transfusions and improving the overall quality of life. Case presentation: A 38-year-old woman was diagnosed with PNH in 2007 and eculizumab therapy was initiated at the end of 2014. She became pregnant in September 2015 and presented various decompensations from forced reductions in therapy due to the nonavailability of eculizumab. The pregnancy was interrupted in week 35, but the well-being of the newborn was not compromised. The patient, however, had to remain hospitalized for resolution of acute kidney insufficiency, anemia, and intense hemolysis, which were reverted by means of intravenous hydration, transfusion of 10 packed red blood cell units, and eculizumab therapy. Conclusion: The rarity of the disease and the lack of protocols for its management during pregnancy hampered the treatment of the patient. However, the symptoms were progressively treated as they appeared, based on laboratory tests since it was necessary to circumvent and handle the lack of eculizumab which was not readily available in Brazil's Public Health System.